Chromosome-level assembly reveals a putative Y-autosomal fusion in the sex determination system of the Greenland Halibut (Reinhardtius hippoglossoides). Issue 1 (15th November 2021) - Ferchaud, Anne-Laure; Mérot, Claire; Normandeau, Eric; Ragoussis, Jiannis; Babin, Charles; Djambazian, Haig; Bérubé, Pierre; Audet, Céline; Treble, Margaret; Walkusz, Wojciech; Bernatchez, Louis
Abstract: Despite the commercial importance of Greenland Halibut ( Reinhardtius hippoglossoides), important gaps still persist in our knowledge of this species, including its reproductive biology and sex determination mechanism. Here, we combined single-molecule sequencing of long reads (Pacific Sciences) with chromatin conformation capture sequencing (Hi-C) data to assemble the first chromosome-level reference genome for this species. The high-quality assembly encompassed more than 598 Megabases (Mb) assigned to 1594 scaffolds (scaffold N50 = 25 Mb) with 96% of its total length distributed among 24 chromosomes. Investigation of the syntenic relationship with other economically important flatfish species revealed a high conservation of synteny blocks among members of this phylogenetic clade. Sex determination analysis revealed that similar to other teleost fishes, flatfishes also exhibit a high level of plasticity and turnover in sex determination mechanisms. A low-coverage whole-genome sequence analysis of 198 individuals revealed that Greenland Halibut possesses a male heterogametic XY system and several putative candidate genes implied in the sex determination of this species. Our study also suggests for the first time in flatfishes that a putative Y-autosomal fusion could be associated with a reduction of recombination typical of the early steps of sex chromosome evolution.